2011
DOI: 10.21101/cejph.a3667
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Accumulation of Creutzfeldt-Jakob Disease in Slovakia - Environmental Metal Imbalance as a Possible Cofactor

Abstract: Slovakia is characterised by an unusually high number of patients affected by genetic Creutzfeldt-Jakob disease (CJD) with E200K mutation at the PRNP gene. Penetrance of the mutation is incomplete (59%). Therefore, for the onset of the clinical manifestation, an influence of other endo-or exogenous factors could not be excluded. Experimental data suggest that copper and manganese levels may play an important role in the pathogenesis of prion diseases. The highest number of Slovak genetic CJD patients originate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Assuming that humans would behave like mice, it remains to determine which life events have increased oxidative insults in offspring that did not in their parents. Moreover, a recent study in the E200K CJD cluster of Slovakia reported an unbalance of manganese/copper concentration in brain tissues of genetic CJD cases in comparison to controls suggesting that metal disequilibrium might act as exogenous co-factor for the development of disease [32], but great caution is needed in the interpretation of these data.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that humans would behave like mice, it remains to determine which life events have increased oxidative insults in offspring that did not in their parents. Moreover, a recent study in the E200K CJD cluster of Slovakia reported an unbalance of manganese/copper concentration in brain tissues of genetic CJD cases in comparison to controls suggesting that metal disequilibrium might act as exogenous co-factor for the development of disease [32], but great caution is needed in the interpretation of these data.…”
Section: Discussionmentioning
confidence: 99%
“…Copper deficiency can cause many types of abnormalities, including anemia, skeletal defects, degeneration of the nervous system, reproductive failure, pronounced cardiovascular lesions, elevated blood cholesterol, impaired immunity, and defects in the pigmentation and structure of hair. Copper is also important for the prevention or moderation of certain neurodegenerative disease, including Parkinson's, Wilson's, Menkes, Alzheimer's, and prion diseases …”
Section: Copper and Neurodegenerative Disordersmentioning
confidence: 99%
“…Copper is also important for the prevention or moderation of certain neurodegenerative disease, including Parkinson's, Wilson's, Menkes, Alzheimer's, [73] and prion diseases. [74][75][76][77][78][79][80][81][82] In many copper-binding enzymes, the biological role of copper involves changing its oxidation state through the following oxidation-reduction reactions:…”
Section: Copper and Neurodegenerative Disordersmentioning
confidence: 99%
“…High Mn 2+ levels and increased Mn 2+ /Cu 2+ ratios were observed in these CJD brains (Slivarichová et al, 2011). The link between Mn 2+ and prion infection was also evidenced at the cellular level (Pass et al, 2015).…”
Section: Prion Protein Binds Transition Metalsmentioning
confidence: 95%